Mental disorders in individuals at risk for exercise addiction – A systematic review. (December 2020) - Colledge, Flora; Sattler, Isabel; Schilling, Hanna; Gerber, Markus; Pühse, Uwe; Walter, Marc
Highlights: It is not clear whether individuals at risk for exercise addiction also suffer from other mental disorders. We review the literature addressing symptoms of mental disorders in those at risk for exercise addiction. The included studies assess eating disorders, depression, anxiety, other addiction and borderline personality disorder. Those at risk of exercise addiction suffer from symptoms of mental disorders more frequently than those not at risk. Abstract: Introduction: Exercise addiction is one of several behavioral addictions which has not yet been designated as an addictive disorder in the Diagnostic and Statistical Manual of Mental Disorders 5 (DSM-5). This is in part due to a lack of clarity concerning co-occurring mental disorders of individuals at risk for exercise addiction. The aim of this review is to summarise the spectrum of psychopathology in populations at risk of exercise addiction. Methods: The MEDLINE, Web of Science and PsycINFO databases were searched. All studies from the date of database creation until February 2020 were considered eligible. Terms used were "exercise addiction" and other mental disorders mentioned in conjunction with substance-related and addictive disorders. Studies were included if they assessed risk for exercise addiction and at least one other mental disorder. Results: Twenty studies were included. The disorders assessed were eating disorders (n = 14), depression (n = 6), anxiety (n = 4), other substance-related and addictive disorders (n = 5), and borderline personality disorder (n = 1). In thirteen of the studies, evidence was found for higher rates of at least one mental disorder (most commonly eating disorders, anxiety and other addictive disorders) in individuals at risk for exercise addiction, compared to those not at risk. Conclusions: Individuals at risk for exercise addiction show a broad range of mental disorders as assessed by self-report, which is in line with sufferers of other addictive disorders. Systematic psychological and clinical assessments in those at risk of exercise addiction are worthwhile, and will serve to characterize the mental health problems of individuals suffering from exercise addiction.